Effect of Ionic Conductivity in Aluminophosphates with Different Organic Structure Directing Templates - Suresh Kumar, B.V.; Byrappa, K.; Ananda, S.; Lokanath Rai, K.M. (Asian Journal of Chemistry, 2010)
The ionic conductivity has been measured for different organic templates in aluminophosphate gels. After crystallization of aluminophosphates under hydrothermal conditions, the conductivity exhibited by these materials arises from the migration of cations through the anion framework cages. The thermodynamic parameters have been evaluated.